2006
DOI: 10.1186/bf03352643
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake probability based on multidisciplinary observations with correlations

Abstract: A number of researchers have formulated earthquake probabilities based on precursory anomalies of multidisciplinary observations in which the underlying assumption is that the occurrence of one precursory anomaly is independent from those of other kinds of anomalies. Observations were classified into two groups, those events followed by an earthquake and those that were not, and the ratio of observed precursors in both groups was taken into consideration. In the present report, recent advances in statistical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Hybrid models with multiplicative probability gains were suggested by the early work of Aki (1981) and Utsu (1982) on conditionally independent earthquake precursors. Later, Imoto (2006Imoto ( , 2007 generalized the notion of multiple earthquake precursors to earthquake probabilities or rates estimated from multidisciplinary observations and showed that multiplicative probability gains could theoretically still be obtained without the independence assumption. See also Faenza and Marzocchi (2010) and Shebalin et al (2014) for applications of a statistical model with multiplicative structure to earthquake forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid models with multiplicative probability gains were suggested by the early work of Aki (1981) and Utsu (1982) on conditionally independent earthquake precursors. Later, Imoto (2006Imoto ( , 2007 generalized the notion of multiple earthquake precursors to earthquake probabilities or rates estimated from multidisciplinary observations and showed that multiplicative probability gains could theoretically still be obtained without the independence assumption. See also Faenza and Marzocchi (2010) and Shebalin et al (2014) for applications of a statistical model with multiplicative structure to earthquake forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…IMOTO (2007) clarified the problem by expressing the probability gain as a quantity of information. For normally distributed observations (or predictive parameters), he derived a formula for the information gain in the general case where multidimensional observations are correlated in both the conditional and background distributions, extending earlier results for multidimensional observations correlated only in the conditional distribution (IMOTO, 2006a). Applying this procedure to three parameters (the Gutenberg-Richter a and b values and the m value, which measures changes in b value) observed in Kanto, central Japan, IMOTO (2008) constructed a seismicity model (referred to as the ABT model) in Kanto, Japan.…”
Section: Introductionmentioning
confidence: 84%
“…Here, by selecting an appropriate unit and origin for variable θ 1 , equation (10) could be satisfied in general. In this case, the IGpe value for observation A 1 , IGpe( A 1 ), can be represented as follows [ Sakamoto et al , 1983; Imoto , 2006]. …”
Section: Multidimensional Normal Distributionmentioning
confidence: 99%
“…If variables θ 1 , θ 2 , … θ n are mutually independent from one another in both distributions, that is, then we assume that f i ( θ i ) and g i ( θ i ) are represented by the following normal distributions: where θ denotes a column vector with components θ 1 ,θ 2 ,.. θ n , and the superscript t refers to the transpose of a matrix. In similar way to the two‐dimensional case [ Imoto , 2006], if it is assumed that for any combination of i and j , θ i and θ j are independent in both the conditional and background joint density distributions, the following equation can be obtained: …”
Section: Multidimensional Normal Distributionmentioning
confidence: 99%
See 1 more Smart Citation